2017
DOI: 10.19173/irrodl.v18i1.2644
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Teacher Networks in Twitter: Are They Related to Community-Based Peer Production?

Abstract: Teachers participate in social networking sites to share knowledge and collaborate with other teachers to create education-related content. In this study we selected several communities in order to better understand the networks that these participants establish in Twitter and the role that the social network plays in their activity within the community, especially related with peer production. We analyzed the topology of these networks in two ways: a) the indirect relations by counting followers and followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…This study also has major methodological implications. Previous studies into online professional learning communities mainly tested relatively small amounts of data using traditional social-science methods, including surveys, interviews, and content analyses, (Britt & Paulus, 2016;Macià & García, 2017;Rodesiler & Pace, 2015). These methods of data collection and analysis tend not only to be time consuming, but also to suffer from the sparse time granularity (Qiu et all, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also has major methodological implications. Previous studies into online professional learning communities mainly tested relatively small amounts of data using traditional social-science methods, including surveys, interviews, and content analyses, (Britt & Paulus, 2016;Macià & García, 2017;Rodesiler & Pace, 2015). These methods of data collection and analysis tend not only to be time consuming, but also to suffer from the sparse time granularity (Qiu et all, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Greenhalgh and Koehler (2017) found that of 3,598 participants, less than 11% posted original tweets; the rest only retweeted or "liked" posts. Macià and García (2017) examined a few Twitter communities for teachers and noticed that while most participants were "connected to less than 80 nodes," small numbers of participants acted as hubs and were connected to a majority of members (p. 117). This kind of unequal participation raises the question of whether users whose participation is limited still benefit from membership in such communities.…”
Section: Twitter For Educators' Professional Development and Learningmentioning
confidence: 99%
“…Here we focus on social presence, which includes open and critical discussion of online material as mediated by group cohesion, open communication, and affective expression. These interactions serve multiple purposes, including supporting cognitive learning (Garrison, Anderson, & Archer, 2010), creating a feeling of being part of a community of learners and developing an identity as a learner in a massive online course (Kizilcec et al, 2017;Macià & García, 2016), and providing opportunities to exchange ideas and co-construct knowledge and even new practices that can be used by other educators (Macià & Garcia, 2017;Macià & García, 2016). Instructors can enhance social interactions through choice of online platform-for example, discussion board versus social media (Clarke & Kinne, 2012;Hou, Wang, Lin, & Chang, 2015;Salmon, Ross, Pechenkina, & Chase, 2015)-and type of discussion question posed (Ke, 2010), as well as by incorporating structured collaborative activities and assessments of collaboration (Collazos, Gonzalez, & Garcia, 2014) and focusing on life experience or case-study analysis (Liu & Yang, 2014).…”
Section: Social Learning In Moocsmentioning
confidence: 99%
“…Sometimes it is assumed that social networks are all online sites which can be accessed through the internet, sometimes it is suggested that there should be clear definitions how social networks are different form Learning Platforms, Learning Management Systems, Virtual Learning environment etc. Authors of this paper will not focus on defining these differences, but rather on benefits of social learning which is supported by using different kind of social media and ICT to scaffold Knowledge Building [29][30][31][32][33][34][35][36][37].…”
Section: Literature Review On the Exploitation Of Social Networking Tmentioning
confidence: 99%
“…Advanced learner profiling methods, developing active, self-directed, responsible learning context with technology [29][30][31], and integrating mobile applications and analysis tools are all examples of the studies concerning smart education research [32,33]. Another important impact of social networks is setting very important milestones for higher education to advance social learning methodologies and practices [34] by the development of new strategies for student centric, and community centric learning.…”
Section: Literature Review On the Exploitation Of Social Networking Tmentioning
confidence: 99%